2020
DOI: 10.1177/1120672120951731
|View full text |Cite
|
Sign up to set email alerts
|

Direct and transsynaptic retrograde degeneration and optic nerve head microvascular changes in patients with hemianopia

Abstract: Purpose: To investigate optic nerve head (ONH) microvascular changes secondary to transsynaptic retrograde degeneration (TRD), comperatively with direct retrograde degeneration and healthy controls. Methods: Patients with hemianopia due to intracranial lesion included in the study. Intracranial lesion was categorized by location: postgeniculate (causing TRD), chiasmal (causing direct retrograde degeneration). For the postgeniculate lesions, the eye on the same side of the lesion was defined as the ipsilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Previous research showed the chiasmal lesion caused more prominent optic nerve head vessel density decrease than postgeniculate lesion, which indicated the direct retrograde degeneration might be more prominent than TRD [22]. And our study shows the RNFL thinning is less prominent than glaucoma' RGCs' degeneration, both of the direct and trans-synaptic retrograde induced by the intracranial tumor.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Previous research showed the chiasmal lesion caused more prominent optic nerve head vessel density decrease than postgeniculate lesion, which indicated the direct retrograde degeneration might be more prominent than TRD [22]. And our study shows the RNFL thinning is less prominent than glaucoma' RGCs' degeneration, both of the direct and trans-synaptic retrograde induced by the intracranial tumor.…”
Section: Discussionsupporting
confidence: 48%
“…Whereas, tumors arising post lateral geniculate body cause damage to the optic radiation after the tertiary neurons in the visual pathway and lead to the trans-synaptic retrograde retinal degeneration (TRD). It also causes the RNFL thinning and the optic nerve head vessel density decrease [18,21,22]. This is mechanically different from the damage of RGCs and axons in glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic cord compression progression led to axonal destruction at the site of compression and cranial compression (Huber et al, 2018 ; Martin et al, 2018 ). Transsynaptic degeneration (TSD)may be related to the decreased excitability of α motoneurons in the spinal cord (Zheng et al, 2017 ), microangiopathy (Celik Buyuktepe et al, 2021 ), and pathological nerve remodeling (Lawlor et al, 2018 ). All of these factors may lead to apoptosis, inflammation, or ischemia, which ultimately mediate neuron damage and are responsible for remote degeneration in spinal cord tracts.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, tumors arising in the post lateral geniculate body cause damage to the optic radiation after the tertiary neurons in the visual pathway and lead to trans-synaptic retrograde retinal degeneration (TRD). It also causes the RNFL thinning and the optic nerve head vessel density to decrease ( 16 , 19 , 20 ). This is mechanically different from the damage to RGCs and axons in glaucoma.…”
Section: Discussionmentioning
confidence: 99%